Mental health problems among health-care workers during the COVID-19 pandemic - Anil Bindu Sukumaran; L Manju; Regi Jose; Meghana Narendran; C Padmini; P NazeemaBeevi; Divija Vijith; R Beena Kumari; Shilpa Prakash; Jithu S. J. Nath; P V Benny (Wolters Kluwer Medknow Publications, 2021)
Introduction: As the pandemic of COVID-19 stretches, its wings across the different parts of the world over the past few months, it is very likely that mental health problems increase, particularly among the health-care workers who have higher risk of exposure to the disease and also to sufferings of the people affected with the disease. Objective: To assess the prevalence and factors associated with depression, anxiety, and stress among health-care workers from Kerala during the COVID-19 pandemic. Materials and Methods: A cross-sectional study among 544 health-care workers from Kerala was conducted by a self-administered online questionnaire in Google Forms by chain referral sampling with Depression, Anxiety, and Stress Scale-21 scale during initial phase of the COVID-19 pandemic. The tests of significance used were Mann-Whitney U-tests and Kruskal-Wallis tests. Odds ratios and 95% confidence interval are estimated. Results: During the early pandemic period, 9.7% of health-care workers had mild depression and 13.3% had moderate-to-severe depression. While 4% had mild anxiety and 3.5% had moderate-to-severe anxiety, about 6.8% had mild stress and 6.4% had moderate-to-severe stress. The anxiety symptoms were significantly higher among nurses compared to doctors. Emotional and social support from higher health authorities is a significant protective factor against stress and depression. Frontline workers have 84% higher risk to have depression. Conclusions: Frontline health-care workers who are directly involved in the screening, diagnosis, treatment, and care for patients with COVID-19 are at higher risk of experiencing poor mental health outcomes. Emotional and social support from higher health authorities is a significant protective factor against depression and stress among health-care workers.